2010
DOI: 10.1016/j.electacta.2009.12.093
|View full text |Cite
|
Sign up to set email alerts
|

Numerical computation of the Faradaic impedance of inlaid microdisk electrodes using a finite element method with anisotropic mesh adaptation

Abstract: Numerical computation of the Faradaic impedance of inlaid microdisk electrodes using a finite element method with anisotropic mesh adaptation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Recently, Michel et al [169] carried out a numerical computation of the faradaic impedance of inlaid microdisk electrodes using a finite-element method and discussed the limitations of the Fleischmann and Pons [168] approach. Calculation of the functions Φ 4 and Φ 5 is shown in Exercise 4.8.…”
Section: Diffusion To Disk Electrodementioning
confidence: 99%
“…Recently, Michel et al [169] carried out a numerical computation of the faradaic impedance of inlaid microdisk electrodes using a finite-element method and discussed the limitations of the Fleischmann and Pons [168] approach. Calculation of the functions Φ 4 and Φ 5 is shown in Exercise 4.8.…”
Section: Diffusion To Disk Electrodementioning
confidence: 99%
“…The classic impedance derivations for this system were by Fleischmann and Pons 16,17 , who recognized that the boundary condition should be uniform concentration across the surface, but for mathematical simplicity used a uniform flux and then averaged the calculated surface concentrations 18 . This was remedied by later workers 19,20 . Michel et al 20 used accurate numerical simulations for the general case of the reaction O + e À R with Butler-Volmer kinetics, and showed that for large standard rate constants the ac concentration was uniform across the surface.…”
Section: Resultsmentioning
confidence: 99%
“…This was remedied by later workers 19,20 . Michel et al 20 used accurate numerical simulations for the general case of the reaction O + e À R with Butler-Volmer kinetics, and showed that for large standard rate constants the ac concentration was uniform across the surface. They showed numerically for fast rates at the reversible potential and with equal diffusivities and bulk concentrations that the mass transport part of the impedance at zero frequency approached 2 in some dimensionless units.…”
Section: Resultsmentioning
confidence: 99%
“…where j stands for the imaginary unit and ω for the pulsation. The boundary condition at the electrode surface is obtained from the linearization of the reaction rate (eq 2) as already described in ref 26.…”
Section: ■ Experimental and Methodsmentioning
confidence: 99%